In vitro conservation of sugarcane germplasm - de Lemos, Eurico Eduardo Pinto; Ferreira, Micheline de Souza; de Alencar, Liduína Maria Calheiros; Neto, Cícero Eduardo Ramalho; de Albuquerque, Marcondes Maurício (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this work was to evaluate the effect of temperature, of sucrose, sorbitol and manitol, as carbon source and osmotic regulator, and of abscisic acid, as growth regulator, on in vitro germplasm conservation of sugarcane. Stem tips of 10 month old plants collected from the sugarcane germplasm bank of the Universidade Federal de Alagoas in Brazil were introduced in vitro and secondary shoots were produced in a multiplication medium. New shoots collected after four subcultures were used in three conservation experiments. There was a positive effect of the low temperature and sucrose as an osmotic regulator and carbon source in maintaining the viability of the explants cultured in vitro. Abscisic acid (1 mg/L) was essential to maintain the explants in a reduced growth condition for 52 weeks without any subculture. The explants promptly returned to normal growth in vitro or were readily acclimatized after 52 weeks of conservation, in the medium with abscisic acid (1 mg/L) plus sucrose (20 g/L) at 15ºC.